Robust flat filtering control of a two degrees of freedom helicopter subject to tail rotor disturbances - Sánchez-Meza, Victor-Gabriel; Lozano-Hernández, Yair; Gutiérrez-Frías, Octavio; Lozada-Castillo, Norma; Luviano-Juárez, Alberto (Zielona Góra: Uniwersytet Zielonogórski)
This article deals with modelling and a flatness-based robust trajectory tracking scheme for a two degrees of freedom helicopter, which is subject to four types of tail rotor disturbances to validate the control scheme robustness. A mathematical model of the system, its differential flatness and a differential parametrization are obtained. The flat filtering control is designed for the system control with a partially known model, assuming the non-modelled dynamics and the external disturbances (specially the tail rotor ones) to be rejected by means of an extended state model (ultra-local model).
Keywords: flat filtering control; generalized proportional integral control; non-linear systems; tail rotor disturbance; two degrees of freedom helicopter